2013
DOI: 10.1002/hed.23315
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation status in laryngeal cancer

Abstract: Laryngeal squamous cell carcinoma (LSCC) belongs to the heterogeneous group of head and neck cancers. In the etiology of LSCC, beside important environmental factors, genetic and epigenetic factors play a role in defining an individual's susceptibility to LSCC.One such epigenetic factor is DNA hypomethylation, which due to the large heterogeneity of the tissue, and invasiveness of the methods used, is often evaluated in easily available tissue, such as peripheral blood, for cancer screening.In this study we ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(153 reference statements)
0
3
0
Order By: Relevance
“…The global loss of DNA methylation in repetitive elements can lead to neighboring gene disruption via transcriptional interference and activation of transposable elements, which can lead to chromosomal and microsatellite instability throughout the genome [ 43 , 86 ]. Global DNA hypomethylation has been studied as a marker of cancer risk in peripheral blood leukocytes [ 87 89 ] and as a biomarker for breast [ 90 ], prostate [ 91 ], ovarian [ 92 ], lung [ 93 ], liver [ 94 ], bladder [ 95 ], oral [ 94 ] and laryngeal cancer [ 96 ]. Our data in GBC tissues and cell lines is consistent with published data for other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…The global loss of DNA methylation in repetitive elements can lead to neighboring gene disruption via transcriptional interference and activation of transposable elements, which can lead to chromosomal and microsatellite instability throughout the genome [ 43 , 86 ]. Global DNA hypomethylation has been studied as a marker of cancer risk in peripheral blood leukocytes [ 87 89 ] and as a biomarker for breast [ 90 ], prostate [ 91 ], ovarian [ 92 ], lung [ 93 ], liver [ 94 ], bladder [ 95 ], oral [ 94 ] and laryngeal cancer [ 96 ]. Our data in GBC tissues and cell lines is consistent with published data for other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed on DNA isolated from histopathologically confirmed laryngeal cancer tissues and adjacent normal laryngeal tissues. Tissue samples were obtained from a homogeneous group of 57 patients (a part of a previously described group) with primary LSCC [8,9]. All the 57 patients were Caucasians from Lower Silesia province in Poland.…”
Section: Global Journal Of Otolaryngology Materialsmentioning
confidence: 99%
“…Laryngeal carcinomas are the most common malignant otorhinolaryngological carcinomas . However, laryngeal squamous cell carcinoma (LSCC) accounts for the majority of laryngeal carcinomas . Surgery, radiotherapy, and chemotherapy remain the major common treatments for LSCC, but the optimal strategy is still unclear .…”
Section: Introductionmentioning
confidence: 99%